"Where My Gays At?" The Status of LGBTQ People and Queer Theory in Nonprofit Research. (June 2022) - Meyer, Seth J.; Dale, Elizabeth J.; Willis, Kareem K. M.
This article critically examines academic scholarship in the field of nonprofit studies that pertains to lesbian, gay, bisexual, transgender, and queer (LGBTQ) people and issues. We introduce the key tenets of queer theory, a critical theory which encourages questioning social constructs, to nonprofit studies as a lens through which to examine the nonprofit sector. Using a queer approach, we analyze the past research on LGBTQ issues along the continuums of whether the research subjects are active or passive participants, and whether the focus on LGBTQ issues is ancillary or central. We find a minority of articles, most written between 2015 and 2019, which position LGBTQ people as central and active participants in the research. We conclude by providing a research agenda for how queer theory can be applied to the nonprofit sector and argue that placing LGBTQ people and organizations as central constituencies in nonprofit research will facilitate social change.